Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Di PT BPRS Al-Washliyah Medan - Syahputra, Reza (Prodi Perbankan Syariah UIN Sumatera Utara Medan, 2025)
The aim of this research is to determine the influence of service quality on customer satisfaction at PT BPRS Al-Wasliyah Medan. This research was conducted on customers of PT BPRS Al-Wasliyah Medan). The type of research used is quantitative research. Sampling used the Porpusive Sampling technique, because the researcher only sampled 91 customer respondents. The data collection technique uses a questionnaire whose validity and reliability have been tested. The results of the research conducted show that the coefficient of determination (adjusted R square) is 0.713 or 71.3%. That Service Quality (Reliability, Responsiveness, Empathy, Assurance, Tangible) influences Customer Satisfaction (Case Study of PT. BPRS Kc Alwasliyan Medan).